Asuhan Keperawatan Pada Bayi BBLR Dengan Penerapan Terapi Nesting Terhadap Saturasi di Ruang Perinatologi RSUD Tangerang - Rini Handayani; Ria Setia Sari; Eni Prihati (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: LBW has emerged as a significant public health issue due to its role as a primary factor contributing to high Infant Mortality Rates (IMRs). LBW stands as one of the major factors leading to increased rates of neonatal, infant, and child mortality, morbidity, and disability. Its implications on their future lives are long-term. Management of LBW can be carried out using invasive methods such as CPAP, supported by developmental care innovations, including nesting.Objective: To understand Nursing Care in patients experiencing LBW, encompassing the processes of application, evaluation, intervention, and assessment with the utilization of nesting innovation for LBW infants receiving CPAP in the Perinatology Ward of Tangerang District General Hospital.Method: Provision of nursing care interventions and implementation of nesting therapy innovations.Results: Following the application of nursing care for three consecutive days, improvements were observed in respiratory frequency, stabilization of infant body temperature, and successful nutrition management.